Analysis of Students' Mathematical Abstraction Ability by Using Problem-Based Learning Model - Zul Fahmi Siregar; Bornok Sinaga; Pardomuan Sitompul (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
This study aims to determine students' mathematical abstraction ability, answer process and difficulties faced by students in solving derivative problems. The subjects in this study were 11th grade students of SMA SWASTA AN - NIZAM Medan who were taught with the application of PBL model and scientific approach. The instrument in this study is a formative test used to see the level of mathematical abstraction ability and the answer process given by students. The difficulties faced by students in the process of solving the problems given can be known through the interview process conducted and documented through cell phones. Of the 19 students who took the math abstraction ability test, 4 students had high category math abstraction ability (21%). 11 students have medium category math abstraction ability (58%), and 4 students have low category math abstraction ability (21%). Of the 4 problems given, for the recognition stage, problem no 1 can be solved by all students. problem no 2 can be solved by 17 students, problem no 3 can be solved by 12 students and problem no 4 can be solved by 8 students. The decline also occurred at the representation and structural abstraction stages. After being analyzed based on the process of answers given by students and the results of interviews conducted, the decline was caused by: 1. the level of difficulty of the problem, 2. learning experience, 3. reasoning power and 4. literacy skills of each different student.. In this research, the media used to help the research process is geogebra. The use of this media is only limited to how to solve the problems given in other ways besides the concepts taught at school.Keywords: Qualitative Research Analysis; Mathematical Abstraction Ability; Problem Based Learning Model